PSYCHOLOGICAL HELP IN LATVIA – REGULATORY FRAMEWORK - Bortaščenoks, Rolands; Purvlīce, Baiba; Mārtinsone, Kristīne; Rancāns, Elmārs; Mihailovs, Ivans Jānis; Ķīvīte – Urtāne, Anda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The field of psychological help in Latvia is undergoing significant changes that require reviewing past practices and professional activities. The term “psychological help” is used quite widely in Latvian regulation, not revealing the semantic difference from other terms as psychological treatment, psychological care, psychological support or psychological aid. The purpose of this article is to find out how the term "psychological help" is used in the regulatory documents of Latvia. The method of qualitative thematic analysis was used to analyse terminology use in selected documents (n115). As a result five topics describing psychological help were identified and defined in the regulatory documents of Latvia: “Professional diversity of psychological help providers”, “Indicators for professional help”, “Targets of professional help”, “Beneficiaries of psychological help”, “Methods of professional help”. The term psychological help in Latvian regulatory documents is revealed in a fragmentary and non-systematic way, which contributes to the confusion of terminological diffusion and boundaries of professional competences.